An overview of the Geoengineering Model Intercomparison Project (GeoMIP). Issue 23 (12th December 2013) - Kravitz, Ben; Robock, Alan; Forster, Piers M.; Haywood, James M.; Lawrence, Mark G.; Schmidt, Hauke
Abstract [1] The Geoengineering Model Intercomparison Project (GeoMIP) was designed to determine robust climate system model responses to solar geoengineering. GeoMIP currently consists of four standardized simulations involving reduction of insolation or increased amounts of stratospheric sulfate aerosols. Three more experiments involving marine cloud brightening are planned. This project has improved confidence in the expected climate effects of geoengineering in several key areas, such as the effects of geoengineering on spatial patterns of temperature and the spatial distribution of precipitation, especially extreme precipitation events. However, GeoMIP has also highlighted several important research gaps, such as the effects on terrestrial net primary productivity and the importance of the CO2 physiological effect in determining the hydrologic cycle response to geoengineering. Future efforts will endeavor to address these gaps, as well as encourage cooperation with the chemistry modeling communities, the impact assessment communities, and other groups interested in model output.